METHODOLOGY FOR DEVELOPING STRIKE POWER IN YOUNG TAEKWONDO PEOPLE - Jumanov Alisher Raxmatkulovich (Research Focus International Scientific Journal, 2024)
This article talks about the importance of increasing the speed of kicking techniques, what factors influence the speed of kicks in the human body and ways to achieve high results.